Factors influencing the success of local craft tourism businesses - Tichaawa, Tembi; Chamboko-Mpotaringa, Mavis (Bulletin of Geography. Socio-economic Series, 2024)
This study examined the factors influencing the success of local craft businesses in sub-Saharan Africa, using Cameroon as a case study. By way of multiple sampling techniques, the study adopted a concurrent embedded mixed-methods research design to collect data from locals (385), tourists (200), and craft vendors (20). Key findings reveal that economic variables, locals’ perceptions of the impacts of tourism and tourists’ preferences influence the success of craft businesses. Statistically significant relationships were found between craft preference attributes such as pricing, cultural significance, and authenticity. The intersection of the stakeholders’ perceptions provides valuable information for policymakers, local authorities, and tourism stakeholders to develop dynamic strategies that maximise the positive impacts of tourism development and craft businesses’ success.